Hypertension management and treatment adherence in patients on permanent hemodialysis therapy - Vaia Raikou; Sotiris Gavriil (Open Exploration Publishing Inc., 2024)
Hypertension (HTN) is connected to many complications such as stroke, heart attack, heart failure, and kidney damage. Aging, lifestyle modifications, and obesity are risk factors associated with arterial HTN. On the other hand, chronic kidney disease (CKD) is a gradually progressive disease that is associated with cardiovascular disease (CVD), HTN, anemia, electrolyte imbalance, acid-base abnormalities, and bone disease. Blood pressure (BP) in hemodialysis patients shows a dynamic nature during dialysis procedures, including intradialytic hypotension and/or intradialytic HTN. Even though hypotensive events are common in hemodialysis sessions, intradialytic HTN, in which the BP increases during and/or immediately after hemodialysis, was associated with a higher mortality risk. The prevalence of intradialytic HTN has been described in 5-20% of hemodialysis treatments. The coexisting comorbidities in CKD patients need adequate pharmacological treatment. As a result, CKD patients are at a high risk for polypharmacy, which causes an elevated risk for adverse drug effects and influences non-adherence to medication. In addition, it is required individualization of medication doses adapted to the decreased renal function according to the progression of CKD. The improvement of health literacy through suitable interventions can facilitate the perception of illness, resulting in high therapy adherence in such a group of patients. This review considers the aspects of HTN management and adherence to the treatment in patients in permanent hemodialysis therapy, contributing to the determination of more effective strategies for improved treatment compliance, aiming at the prevention of CVD in this patient population.